2023
DOI: 10.1038/s41598-023-30240-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antioxidant double-layered nanofibrous mat promotes wound healing in diabetic rats

Abstract: Diabetic wounds are problematic to heal owing to microbial infections as well as decreased proliferation and high concentrations of reactive oxygen species. In this study, a double-layered nanofibrous mat containing grape seed extract (GSE) and silver sulfadiazine (SSD) was fabricated. A synthetic biodegradable polymer, e.g., polycaprolactone (PCL), and a natural material (i.e., collagen) were employed as wound dressing substances. The results showed that GSE possesses antioxidant activity which can be helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…In the diabetic group analysed in the present research, corne-ocyte surface area tended to increase above the control level, with an increase in the num-ber of keratinocytes in the stratum corneum (Figure 1). These results suggested that the turnover of epidermal cells in experimentally induced diabetic mice has a tendency to slow down (Figure 4) [17][18][19][20].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the diabetic group analysed in the present research, corne-ocyte surface area tended to increase above the control level, with an increase in the num-ber of keratinocytes in the stratum corneum (Figure 1). These results suggested that the turnover of epidermal cells in experimentally induced diabetic mice has a tendency to slow down (Figure 4) [17][18][19][20].…”
Section: Discussionmentioning
confidence: 89%
“…Our study is individualized by the identification of morphological lesions and cellu-lar features in the diabetic tegument, which have both functional and etiopathogenic implications for the healing of subsequent lesions [8,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the therapeutic efficiency of PC for the treatment of numerous diseases, such as oxidative stress-induced brain injuries, cancer, and wounds, , the PCgels can be useful as a therapeutic injectable filler for brain tissue. For that, initial burst release of the PC from the hydrogels can be effective for protection of the neuronal cells against oxidative stress through rapid ROS clearance and less inflammation at the early stage of the disease. , The release kinetics of the drugs encapsulated in the hydrogel network can be tuned by polymeric crosslinking density and its swelling behavior. Therefore, we examined that all our PCgels were shear-thinning, and no significant changes in viscoelasticity of the hydrogels were observed even after the addition of collagen and encapsulation of PC (Figure S3a–c).…”
Section: Resultsmentioning
confidence: 99%
“…As studies have shown, electrospinning is a versatile and simple method to fabricate micro and nanofibers in different forms. Additionally, synthetic and natural polymers and hybrid materials can be electrospun into micro and nanofibers 4 , 5 . Electrospinning techniques possess numerous usages in the manufacturing of filters, soft tissue prosthetics, tissue engineering scaffolds, reinforced composites, porous electrodes for battery separators, protective garments, and controlled drug delivery 6 .…”
Section: Introductionmentioning
confidence: 99%